2019
DOI: 10.3390/nu11092157
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Vitamin C and E levels in Cardiac Surgery Patients and Their Clinical Significance

Abstract: Background: Oxidative stress contributes to organ dysfunction after cardiac surgery and still represents a major problem. Antioxidants, such as vitamins C and E might be organ protective. Methods: The primary objective of this prospective observational study was the description to evaluate the perioperative vitamin C and E levels in 56 patients undergoing cardiac surgery with the use of cardiopulmonary bypass. The association of vitamin C with inflammatory reaction, oxidative stress, organ dysfunctions, and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
0
25
0
2
Order By: Relevance
“…The results are also in accordance with the study of Hill et al, who reported no significant differences regarding postoperative inflammatory response as assessed by mean postoperative WBC levels (p ¼ 0.677). 21 In 2012, Jouybar et al 22 performed a similar, but smaller study investigating the effect of perioperative supplementation of AA in 40 elective on-pump CABG patients. No significant difference between the study groups regarding the postoperative inflammatory response as well as kidney function was identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are also in accordance with the study of Hill et al, who reported no significant differences regarding postoperative inflammatory response as assessed by mean postoperative WBC levels (p ¼ 0.677). 21 In 2012, Jouybar et al 22 performed a similar, but smaller study investigating the effect of perioperative supplementation of AA in 40 elective on-pump CABG patients. No significant difference between the study groups regarding the postoperative inflammatory response as well as kidney function was identified.…”
Section: Discussionmentioning
confidence: 99%
“…The results are also in accordance with the study of Hill et al, who reported no significant differences regarding postoperative inflammatory response as assessed by mean postoperative WBC levels ( p = 0.677). 21 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, surgical information such as the length of surgery, type of anaesthetic and surgical complications were only reported in 4 trials. (60,62,71,72) Various studies did take into account a range of additional vital biomarkers including vitamin E concentrations, haematocrit concentrations indicative of hemodilution, (66) biomarkers of oxidative stress (44,45) and the type of anaesthetic administered. (60) Gender differences were only considered in one trial, (47) which were averaged for the purpose of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Only studies presenting with a low to unclear risk of bias were included into the meta-analysis (Figure 2), with those reporting a high risk of bias on at least one of the assessment domains being excluded from the meta-analysis (Figure 3). Mean pre-operative vitamin C concentrations varied between studies, with only three studies (49,59,71) reporting mean plasma vitamin C concentrations indicative of a inadequate/deficient concentration (< 28 µmol/L). (75) Twenty-one studies assessed plasma vitamin C concentrations within 7 days post-operatively.…”
Section: Meta-analysismentioning
confidence: 99%
“…Die normale Plasmakonzentration von Vitamin C liegt bei 50-80 μmol/l (0,9-1,44 mg/dl). Bei Werten < 50 μmol/l liegt ein suboptimaler Vitamin-C-Status vor [21]. Eine Hypovitaminose wird definiert über eine Konzentration < 23 μmol/l.…”
Section: Vitamin-c-mangelunclassified